Gas diffusion layers for fuel cells
By introducing characteristic gradient design into the gas diffusion layer of the fuel cell, the problem of uneven current density distribution in the fuel cell is solved, and more efficient fuel cell performance is achieved.
Patent Information
- Application Number
- CN202080077629.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-11-20
- Filing Date
- 2020-11-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2040-11-05
AI Technical Summary
In the operation of fuel cell, the current density distribution is uneven due to the gradient between chemical composition and operating parameters between supply and discharge, which affects the performance of the fuel cell.
A gas diffusion layer (GDL) with a characteristic gradient, in which the planar conductive fiber material and microporous layer (MPL) have gradients of chemical and physical properties on the substrate surface, improve the distribution of the operating medium through this structure.
Through the GDL with the characteristic gradient, the power of the fuel cell is significantly improved, the fluctuation of the current density on the active surface is reduced, and the performance of the fuel cell is improved.
Smart Images

Figure BDA0003631767620000161 
Figure BDA0003631767620000171 
Figure HDA0003631767630000011
Abstract
Description
Field of the Invention
[0001] The present invention relates to a gas diffusion layer for a fuel cell, a fuel cell comprising the same and the use of the gas diffusion layer. Background Art
[0002] Fuel cells generate electricity by chemically reacting fuel, especially hydrogen, with oxygen to produce water. In hydrogen-oxygen fuel cells, hydrogen or a hydrogen-containing gas mixture is supplied to the anode, where electrochemical oxidation occurs and releases electrons (H2 → 2H + +2e - ). Protons are transported from the anode space into the cathode space via a membrane that separates the reaction spaces gas-tightly from one another and is electrically insulating. The electrons provided at the anode are fed to the cathode via an external conductor circuit. Oxygen or an oxygen-containing gas mixture is supplied to the cathode, wherein the reduction of oxygen occurs under the condition of receiving electrons. The anions of oxygen formed in this process react with the protons transported through the membrane to form water (1 / 2O2+2H + +2e - →H2O).
[0003] Low temperature proton exchange membrane fuel cells (PEMFC, proton exchange membrane fuel cells, also known as polymer electrolyte membrane fuel cells) are used in many applications, especially in automotive powertrains, with efficiencies of up to 60%. The core of the PEMFC is a polymer electrolyte membrane (PEM), which is permeable only to protons (or hydronium ions H3O+) and water, and spatially separates the oxidant (usually oxygen in the air) from the reductant. A humidified membrane is usually used to ensure the best possible proton transport via the membrane. A catalyst layer is applied to the anode and cathode sides of a gas-tight, electrically insulating, proton-conducting membrane, which constitutes an electrode and generally contains platinum as a catalytically active metal. The actual redox reaction and charge separation occur in the catalyst layer. Because it must be both electronically conductive and proton-conductive, and additionally must allow the supply of reaction gases and the discharge of water formed in the cathode reaction, special requirements are placed on it. The unit formed by the membrane and the catalyst layer is also referred to as a CCM (catalyst coated membrane). There is a gas diffusion layer (GDL) on both sides of the CCM, which stabilizes the structure of the cell and assumes the function of transporting and distributing the reaction gases, water, heat and current. The membrane, electrodes and gas diffusion layer form a membrane electrode unit (MEA, membrane electrode assembly).
[0004] An alternative to CCMs is a gas diffusion electrode (GDE), in which the electrode material is not applied to the membrane, but to the GDL. EP 2228857 A1 describes a membrane electrode unit for a high-temperature fuel cell, comprising a gas diffusion electrode having at least two gas diffusion layers containing polytetrafluoroethylene, wherein the gas diffusion layers have different polytetrafluoroethylene concentrations. The GDE thus has a PTFE concentration gradient in the flow direction of the operating medium, i.e. with respect to its thickness or perpendicular to the base surface (i.e. in the direction of the z-axis).
[0005] In a single cell with only a single membrane electrode unit, a flow distribution plate is arranged on each side of the MEA, the flow distribution plate having channels for supplying process gas to the electrodes and additional internal cooling channels, which are usually used for heat dissipation. However, a fuel cell is usually not composed of a single cell, but of a plurality of membrane electrode units arranged in a stack, which are connected in series and whose electrical powers are added. Thus, usually only one flow distribution plate (so-called bipolar plate) is arranged between two membrane electrode units. The bipolar plate is structured on the front and rear sides and has channels for supplying process gas to the cathode adjacent on one side and the anode adjacent on the other side, respectively, as well as usually additional internal cooling channels. The flow distribution plate or bipolar plate is composed of an electrically conductive material in order to establish an electrical connection between the stacked membrane electrode units.
[0006] The main task of the flow distributor plate is to uniformly supply the reaction gases to the MEA and to discharge the reaction products, i.e. the water formed in the cathode reaction in the case of hydrogen and oxygen fuel cells. For this purpose, the flow distributor plate between the supply and the discharge has a channel structure open on one side, the so-called flow field. The flow field serves to macroscopically distribute the reaction gases to the adjacent GDL, which takes on the microscopic distribution on the catalytically active area of the membrane. The flow field is also used to discharge gaseous and liquid product water. The flow field is formed by webs and channels, the arrangement of which forms a unique design. Common web widths and channel widths are in the range of about 0.2 to 1.5 mm, respectively. Four main flow field designs are currently used in PEMFC:
[0007] Parallel flow fields with straight channels, meander flow fields, cross flow fields with interrupted channels and back flow fields. When designing the flow field, in addition to the process gas supply, constant condensate discharge is also an important criterion. Inside the flow field, convective mass transfer dominates due to the pressure difference between the inflow and outflow of the flow field. The anode and cathode differ in their requirements regarding the supply of process gas and the discharge of reaction products. On the anode side, the supplied hydrogen is essentially converted into protons, which migrate through the membrane to the cathode. No process water is produced in the anode reaction, but water can reach the anode from the cathode through the membrane. On the cathode side, a significant amount of water is produced by the reduction reaction, which must be discharged via the channel structure of the flow distribution plate. Therefore, the two sides of the flow distribution plate or bipolar plate for the cathode and anode usually have different flow fields.
[0008] There is a gas diffusion layer between the flow distribution plate or the bipolar plate and the catalyst layer, which is of great significance to the function and performance of the fuel cell:
[0009] All process components consumed and generated in the electrode reactions must be transported through the gas diffusion layer and evenly distributed from the macrostructure of the flow distributor plate / bipolar plate to the microstructure of the catalyst layer. This includes the transport of hydrogen to the anode, oxygen to the cathode, and gaseous and liquid water from the anode into the flow channels of the flow distributor plate / bipolar plate. In this case, on the one hand, the transport of the gas should not be hampered by overfilling of the pores, and on the other hand, the MEA should not dry out.
[0010] The electrons formed and consumed in the half-cell reaction must be directed to the flow distribution plate with the lowest possible voltage loss. This is achieved by using highly conductive materials.
[0011] The heat generated in the reaction must be discharged to the coolant in the flow distribution plate, so the material of the GDL must also have sufficient thermal conductivity.
[0012] In addition, the GDL must also serve as a mechanical balance between the macrostructured flow distributor plate and the catalyst layer. To this end, component tolerances must be compensated and compression pressures must be distributed. It also serves to mechanically protect the very thin membranes, which are exposed to high loads in the fuel cell.
[0013] Due to the required properties, GDL usually consists of a carbon fiber substrate, which is usually hydrophobically equipped with a fluoropolymer (such as PTFE). In order to optimize the transport properties of gas and liquid water, GDL is usually coated with a microporous layer (MPL). MPL usually consists of a fluoropolymer (such as PTFE) as a binder and a porous and conductive carbon material (such as carbon black or graphite powder). While the diameter of the pores in the fiber substrate of GDL is usually 10 to 30 μm, the diameter of the pores in MPL is usually in the range of 0.05 to 1 μm. Since the pore size of the electrode is in the range of 10 to 100 nm, the transition from the macropores of the substrate to the micropores of the electrode is achieved by MPL. Currently, GDL uses the following three materials as carbon fiber substrates:
[0014] - Carbon fiber fabrics: For example, yarns made of oxidized but not yet carbonized polyacrylonitrile fibers are used in the production, which are carbonized or graphitized after weaving.
[0015] Carbon fiber paper: For example, in the production PAN fibers are carbonized, crushed into fiber fragments, dissolved, and similar to papermaking, the fiber fabric is produced by screening (handmade paper). To stabilize the paper, a binder is used, such as a phenolic resin.
[0016] Carbon fiber nonwovens: For production, dried, carded and water jet-cured oxidized polyacrylonitrile nonwovens can be used, which are then calibrated for thickness and carbonized. Conductive nonwovens and their production are described, for example, in WO 02 / 31841 A2.
[0017] The GDL known from the prior art consists of layers and substructures that are as homogeneous as possible. So far, neither the fiber structure nor the hydrophobic finishing and MPL coating had any particularly developed property gradients.
[0018] In addition, there is the problem in the operation of fuel cells that there are large differences in the chemical composition of the flowing operating medium (oxygen content, hydrogen content, total water content) and operating parameters (temperature, pressure, gaseous and liquid water content) between the flow field for supplying process gas to the flow distribution plate and the discharge of reaction products from the flow field. Many of these parameters have gradients not only relative to the specific flow curve predetermined by the flow field design, but also relative to the direct connection between the supply and discharge of the operating material. These gradients continue in the GDL all the way to the electrodes. It has a great influence on the performance of the fuel cell because it leads to a gradient in the current density distribution between the input and output of the corresponding electrode. Here, the gradient on the cathode side (air side) of the fuel cell determines the power, wherein gradients in the hydrogen distribution and the water passing through the membrane and the gradient formation associated therewith may also occur on the anode side. This gradient formation is explained below for the situation at the cathode:
[0019] Cathode input terminal:
[0020] O2 concentration = maximum
[0021] O2 pressure = maximum
[0022] Temperature = minimum
[0023] Gas humidity = minimum
[0024] Cumulative liquid water volume = minimum
[0025] Cathode output terminal:
[0026] O2 concentration = minimum
[0027] O2 pressure = minimum
[0028] Temperature = Maximum
[0029] Gas humidity = maximum
[0030] Cumulative liquid water volume = maximum
[0031] Attempts have been made to reduce the formation of such gradients during fuel cell operation. One approach is the design of the flow distributor plate / bipolar plate. Thus, attempts are made to minimize the formation of gradients by designing the flow field (e.g. cross-flow and counter-flow of anode and cathode gases).
[0032] WO 2015150533 describes a bipolar plate for a fuel cell, the hydraulic cross section of which is optimized, thereby reducing the pressure loss of the operating medium and achieving the most uniform pressure distribution of the operating medium on the surface. For this purpose, a bipolar plate is used, which is divided into three areas, including two distribution areas and an active area. Here, the first distribution area is used to introduce the operating medium into the active area of the bipolar plate, and the second distribution area is used to discharge the operating medium from the active area. In addition, the bipolar plate has a channel, which connects the main ports of the operating medium of the two distribution areas to each other. In addition, the distribution area has at least one overlapping section, in which the channels overlap each other without fluid communication. The cathode gas main port is arranged so that the cathode channel extends straight from the cathode gas main port on at least the distribution area of the fuel cell, and in the first overlapping section, the anode channel and the cathode channel starting from the anode gas main port overlap each other and enclose an angle greater than 0° and less than 90°. The fuel cell described in WO 2015150533 still needs to be improved in its characteristics.
[0033] DE 102005022484 A1 describes a gas diffusion layer having at least two functional regions operatively connected to each other, wherein the first region has a porous structure and the second region is designed as a stabilization zone. In general and without being supported by embodiments, it is described that the GDL can have a progressive structure, for example in the form of a gradient. For example, the GDL can consist of a uniform material, which is characterized by gradients along different spatial directions with respect to its bending stiffness, its tensile modulus or other mechanical properties not specified in detail. In particular, there is no description in this text of a GDL coated with an MPL, which has a continuous or jumping characteristic gradient in the xy plane and which changes monotonically depending on the position (i.e., it either always increases or always decreases, so that the gradient can also remain constant in a sub-region, but does not have a local minimum or maximum value).
[0034] US 2010 / 0255407 A1 describes an electrode for a fuel cell, which includes a gas diffusion layer, a catalyst layer and a waterproof material at the interface between the gas diffusion layer and the catalyst layer. Specifically, it relates to a special embodiment of a PEM fuel cell with an electrolyte membrane impregnated with phosphoric acid. The waterproof material is to prevent phosphoric acid from blocking a uniform oxygen flow from entering the catalyst layer. It has a continuous concentration gradient in a first direction extending away from the gas diffusion layer (i.e., in the z direction) and a discontinuous concentration gradient in a second direction perpendicular to the first direction (i.e., in the x, y plane). The waterproof material between the GDL and the catalyst layer is a basic feature of the electrode, wherein the waterproof material does not correspond to the MPL, which can also exist separately. In addition, it is crucial that the waterproof material has a discontinuous gradient in the surface direction at the interface between the GDL and the catalyst layer. To this end, the waterproof material can be arranged on the GDL, for example, in a dotted manner, wherein the point has a radial concentration gradient in the direction of the surface. It is also not described herein to coat the GDL with an MPL having a monotonic characteristic gradient that is continuous or jumpy in the x, y plane.
[0035] CN 110112425 describes a PEM fuel cell with a gas diffusion layer having a hydrophobicization of a fiber material along a flow channel having a gradient in the main gas flow direction between the inlet and the outlet. The hydrophobicization is preferably performed using PTFE. In this case, the fiber material itself is hydrophobicized. The use of a GDL with MPL as an additional layer having a monotonic characteristic gradient in the x,y plane is not described herein.
[0036] There is a need for PEM fuel cells which are improved with regard to the complex characteristic curves described. The object of the invention is to reduce or avoid disadvantages caused by gradients with regard to the chemical composition and / or operating parameters between the supply and discharge of the operating medium. The proposed fuel cell should be distinguished in particular by the smallest possible fluctuations in the current density on the active surface.
[0037] Surprisingly, it has now been found that this object is achieved by a gas diffusion layer for a fuel cell, which itself has at least one property gradient, whereby the distribution of the operating medium via the GDL is improved. By specifically adapting the GDL properties to the gradient of the operating medium, as predetermined by the ambient conditions of the half-cell reaction, the power of the fuel cell can be significantly increased. In particular, fluctuations in the current density on the active surface can be reduced. Summary of the invention
[0038] A first subject of the present invention is a gas diffusion layer for a fuel cell, comprising
[0039] a) a planar conductive fiber material, and
[0040] b) a microporous layer on one of the surfaces of the fiber material,
[0041] The gas diffusion layer has at least one property gradient with respect to its base area (in the x, y plane) with respect to at least one chemical and / or physical property.
[0042] In a preferred embodiment, at least the microporous layer has at least one property gradient.
[0043] Another subject of the invention is a method for producing a gas diffusion layer for a fuel cell, the gas diffusion layer comprising a) a planar electrically conductive fiber material and b) a microporous layer on one surface of the fiber material, wherein the microporous layer has at least one property gradient with respect to the base surface of the gas diffusion layer (in the x, y plane) with respect to at least one chemical and / or physical property, wherein
[0044] i) providing a planar conductive fiber material a),
[0045] ii) coating the fiber material provided in step i) with a precursor to form a microporous layer, wherein the composition of the precursor is changed during coating to produce a gradient,
[0046] iii) subjecting the coated fiber material obtained in step ii) to a thermal aftertreatment.
[0047] Another subject matter of the invention is a fuel cell comprising at least one gas diffusion layer as defined above and below.
[0048] A further subject matter of the invention is the use of a gas diffusion layer as defined above and below for producing a fuel cell having reduced current density fluctuations on the electrode side, in particular on the cathode side.
[0049] Description of the invention
[0050] The fuel cell according to the present invention has the following advantages:
[0051] By virtue of the at least one characteristic gradient of the gas diffusion layer according to the invention, the properties of the GDL can be specifically adapted to the operating conditions of the corresponding fuel half-cell. The GDL is characterized by improved properties of the operating material distribution. In particular, the GDL can independently control different transport processes. Thus, for example, the transport of liquid water and gaseous water can be regulated separately. The transport of oxygen to the cathode via the GDL can also be specifically controlled.
[0052] The gas diffusion layer according to the invention can be produced simply and cost-effectively.
[0053] By using the gas diffusion layer according to the invention, fluctuations in the current density over the active surface can be reduced in the resulting fuel cell.
[0054] Gas Diffusion Layer (GDL)
[0055] The GDL used according to the present invention is a planar structure with a substantially two-dimensional plane size and a relatively small thickness. The gas diffusion layer according to the present invention has a base surface, which generally corresponds substantially to the base surface of the adjacent membrane with a catalyst layer and the base surface of the adjacent flow distribution plate. For example, the shape of the base surface of the gas diffusion layer can be a polygon (n>3 n-gon, such as a triangle, a quadrilateral, a pentagon, a hexagon, etc.), a circle, a circle segment (such as a semicircle), an ellipse or an ellipse segment. Preferably, the base surface is a rectangle or a circle. Within the scope of the present invention, an orthogonal coordinate system is used to describe the GDL, wherein the base surface of the GDL is located in a plane spanned by the x-axis and the y-axis (also referred to as the x, y plane). The z-axis orthogonal thereto is used to describe the material thickness. According to the description commonly used for fiber composite materials, the x-axis is also described as the roll direction (machine direction, MD), and the y-axis is described as the counter-roll direction (direction across the machine, CMD). In the direction of the z-axis, mass transfer is basically carried out between the flow distribution plate and the membrane.
[0056] According to the invention, the gas diffusion layer has at least one property gradient with respect to at least one chemical and / or physical property. That is, at least one property of the gas diffusion layer depends on the position. The property gradient can extend in one, two or all three spatial directions. It can extend over the entire longitudinal extension in a spatial direction or in a specific section, respectively. The property change can be sudden (that is, the gas diffusion layer according to the invention has inhomogeneity in at least one property) or continuous (that is, the gas diffusion layer according to the invention has heterogeneity in at least one property). The sudden property change generally has at least 2 steps, preferably at least 3, and in particular at least 4, in terms of the property with the gradient. The planar fiber material a) and the microporous layer b) and both can have at least one property gradient.
[0057] Preferably, at least the microporous layer has at least one characteristic gradient. Preferably, at least the gas diffusion layer of the cathode side of the fuel cell according to the invention has an MPL having a characteristic gradient relative to the base surface of the GDL (in the x, y plane). It has been found that by using an MPL having a characteristic gradient relative to the base surface of the GDL (in the x, y plane), a more uniform current density distribution of the fuel cell can be achieved. In a specific embodiment, only the microporous layer has one or more characteristic gradients.
[0058] Preferably, the gas diffusion layer (i.e. the planar fiber material A) and / or the microporous layer B) has at least one characteristic gradient, which changes monotonically as a function of the position. A monotonic characteristic change is understood to mean that the value of the function representing the characteristic change always increases or always decreases when the value for the position coordinate increases. It is possible for the function value representing the characteristic change to remain the same over the course of the position coordinates across a sub-region or across a plurality of sub-regions. However, it does not have local minima or maxima.
[0059] Preferably, the gas diffusion layer (i.e. only the planar fiber material A), or only the microporous layer B), or the planar fiber material A) and the microporous layer B) have only characteristic gradients that vary monotonically as a function of position. Preferably, at least the microporous layer b) has at least one characteristic gradient that varies monotonically as a function of position. In a specific embodiment, only the microporous layer has at least one characteristic gradient that varies monotonically as a function of position. In another specific embodiment, the microporous layer has only a characteristic gradient that varies monotonically as a function of position.
[0060] In particular, the microporous layer has only one characteristic gradient, and this characteristic gradient changes monotonically as a function of position.
[0061] The gas diffusion layer comprises at least one electrically conductive, planar fiber material as component a). Preferably, component a) comprises a fiber material selected from the group consisting of nonwovens, paper, woven fabrics and combinations thereof.
[0062] Suitable substrate materials are fiber materials which are themselves electrically conductive or which are made electrically conductive by the addition of conductive additives (e.g. carbon or metal particles). Suitable substrate materials are in principle carbon fibers, glass fibers, organic polymer fibers (e.g. polypropylene, polyester, polyphenylene sulfide, polyether ketone and mixtures thereof). The fibers contained in the fiber material a) preferably include carbon fibers (carbon fibers, carbon fibers) or consist thereof. Such fiber materials particularly advantageously meet the requirements of the GDL for gas diffusivity, liquid water permeability, electrical conductivity and thermal conductivity.
[0063] The preparation of carbon fiber can be carried out in a conventional manner, wherein polyacrylonitrile fiber (PAN fiber) is preferably used as the starting material. PAN fiber is prepared by free radical polymerization of a monomer composition, and the monomer composition preferably contains at least 90 weight percent acrylonitrile, based on the total weight of the monomers used for polymerization. For example, by wet spinning and coagulation spinning, the obtained polymer solution is spun into filaments and merged into a melt. Before the PAN precursor is converted into carbon fiber at high temperature, it is usually subjected to oxidative cyclization (also referred to as oxidation) at an elevated temperature of about 180 to 300° C. in an oxygen-containing environment. The chemical crosslinking thus produced improves the dimensional stability of the fiber. Subsequently, actual pyrolysis into carbon fiber is carried out at a temperature of at least 1200° C. For this pyrolysis, starting fibers or planar fiber materials can be used, depending on the shape of the fiber material sought. Depending on the temperature during pyrolysis, carbonization and graphitization are distinguished. Carbonization refers to a treatment carried out at about 1200 to 1500° C. in an inert gas environment, which results in the separation of volatile products. So-called high modulus fibers or graphite fibers are obtained by graphitization, i.e. heating under inert gas to about 2000 to 3000° C. These fibers are pure, lightweight, strong, and have good electrical and thermal conductivity.
[0064] The fiber material a) is preferably selected from the group consisting of carbon fiber woven fabrics, carbon fiber papers and carbon fiber nonwovens.
[0065] In carbon fiber fabrics, the planar fiber material is produced by crossing two yarn systems, warp (warp yarns) and weft (weft yarns). As in textiles, the fiber bundles are connected together in a flexible but non-detachable manner. For the production of carbon fiber fabrics, oxidized but not yet carbonized or graphitized PAN fibers are preferably used. Carbonization or graphitization is carried out after weaving to give the planar fiber material conductivity.
[0066] As mentioned at the beginning, oxidized PAN fibers are usually used to prepare carbon fiber paper. It is crushed into fiber fragments, pulped, and similar to papermaking, a fiber fabric is prepared by screening (handmade paper) and dried. In a preferred embodiment, at least one binder is additionally introduced into the paper. For example, suitable binders are phenol resins, furan resins, polyimide resins, etc. In order to introduce the binder, the paper can be impregnated with the binder and the binder can be optionally subsequently cured. After impregnation and hardening, the carbon fiber paper is subjected to carbonization / graphitization again so as to also convert the binder into a compound with improved conductivity. In another suitable embodiment, in order to provide the fiber material a), a filled carbon fiber paper is used. First, it is prepared as described above, but instead of introducing the binder and carbonization / graphitization, a filler made of a carbon material in a polymer binder is introduced into the still wet paper. For this purpose, a carbon polytetrafluoroethylene filler is particularly used. Through this filling, thermal conductivity and electrical conductivity are improved, so that carbonization / graphitization can be eliminated.
[0067] To produce carbon fiber nonwovens, unoxidized or oxidized PAN fibers can be used. In a first step, these can be dry-laid (combed) to form a fleece and then solidified into a nonwoven. This can be done, for example, by water jet felting (hydroentanglement), so that the carbon fibers are oriented, entangled and thus mechanically stabilized.
[0068] Optionally, the thickness of the cured nonwoven can be calibrated to the desired value. After the nonwoven is laid and cured, the nonwoven based on unoxidized PAN fibers is first oxidized at an elevated temperature and in an oxygen environment and then carbonized / graphitized in an inert gas environment. The nonwoven based on oxidized PAN fibers is only subjected to carbonization / graphitization after the nonwoven is laid and cured. Optionally, at least one binder can be additionally introduced into the nonwoven and optionally subsequently cured. Suitable binders are those used for carbon fiber paper, in particular phenolic resins. For example, the introduction of the binder can be carried out after carbonization / graphitization, and the impregnated nonwoven obtained is finally carbonized / graphitized again.
[0069] In a particular embodiment, the planar electrically conductive fiber material a) comprises at least one carbon fiber nonwoven. Furthermore, it is advantageous because it is compression elastic and can be produced simply on a large scale, for example in a roll-to-roll process.
[0070] The fiber material a) is usually a fiber composite material, including:
[0071] a1) Carbon fiber,
[0072] a2) optionally at least one polymer binder and / or a pyrolysis product thereof,
[0073] a3) optionally at least one further additive different from a2).
[0074] The fiber material a) contained in the gas diffusion layer can contain customary additives a3). These are preferably selected from the group consisting of hydrophobizing agents, conductivity-increasing additives, surface-active substances and mixtures thereof.
[0075] In order to improve the transport processes through the GDL and at the interface, it may be advantageous to increase the hydrophobicity of the fiber material a).
[0076] Suitable hydrophobing agents are fluoropolymers, such as polytetrafluoroethylene (PTFE) and tetrafluoroethylene-hexafluoropropylene copolymers (FEP). PTFE is preferably used as the hydrophobing agent. The fiber material can be provided with the hydrophobing agent by conventional impregnation methods. For this purpose, a PTFE dispersion can be applied in an impregnation bath, the solvent evaporated and the treated fiber material sintered at an elevated temperature of generally at least 300° C.
[0077] Preferably, the fiber material a) has a hydrophobizing agent content of 3 to 40 weight percent based on the total weight of the fiber material a). In a specific embodiment, the fiber material has a PTFE content of 3 to 40 weight percent based on the total weight of the fiber material a).
[0078] In order to improve the electrical and thermal conductivity, the fiber material a) can be provided with at least one conductivity-improving additive. Suitable conductivity-improving additives are, for example, metal particles, carbon particles, etc. Preferably, the conductivity-improving additive is selected from carbon black, graphite, graphene, carbon nanotubes (CNT), carbon nanofibers and mixtures thereof. The finishing of the fiber material a) with at least one conductivity-improving additive can be carried out, for example, together with a hydrophobic agent, in particular a PTFE dispersion. In many cases, the fiber material a) has good electrical and thermal conductivity due to the carbon fibers used, even without the conductivity-improving additive.
[0079] Preferably, the fiber material a) has a content of 0 to 40 weight percent of conductivity-improving additives, based on the total weight of the fiber material a). If the fiber material a) contains conductivity-improving additives, this is preferably in an amount of 0.1 to 40 weight percent, particularly preferably 0.5 to 30 weight percent, based on the total weight of the fiber material a).
[0080] The fiber material a) preferably has a thickness of 50 to 500 μm, particularly preferably 100 to 400 μm. This thickness relates to the fiber material a) in the uncompressed state, ie before the GDL is installed in the fuel cell.
[0081] The fiber material a) preferably has a porosity of 10 to 90%, more preferably 20 to 85%. The porosity of the fiber material can be calculated from the measured thickness and the measured weight per unit area at a known fiber density. Thus, for 1.8 g / cm 3 Carbon fiber density: Porosity [%] = [(1.8 unit area weight / thickness) / 1.8] × 100. In addition, the density of the gas diffusion layer can be determined by helium density measurement, and the specific pore volume can be determined by mercury porosimetry measurement. The porosity is calculated as follows: Porosity [%] = specific pore volume / (specific pore volume + 1 / He density) x 100%. ]
[0082] The average pore diameter of the fiber material a) is preferably in the range from 5 to 60 μm, particularly preferably from 8 to 50 μm, in particular from 10 to 40 μm. The average pore diameter can be determined by mercury porosimetry.
[0083] The gas diffusion layer according to the invention consists of a two-layer composite based on a planar electrically conductive fiber material a) and a microporous layer (MPL) b) on one surface of the fiber material a).
[0084] In contrast to the macroporous fibrous material a), MPL is microporous, with a pore size generally significantly below one micrometer, preferably up to 900 nm, particularly preferably up to 500 nm, and in particular up to 300 nm. The average pore size of the MPL b) is preferably in the range of 5 to 200 nm, particularly preferably in the range of 10 to 100 nm. The determination of the average pore size can also be carried out by mercury porosimetry. The last-mentioned average pore size is particularly suitable for the use of carbon black as conductive particles in MPL. By using graphite as a conductive particle or using a pore former in MPL, significantly larger MPL pores can also be produced. Depending on the composition, the average pore diameter is greater than 1 μm. When different conductive particles are used, the pore size can have a bimodal or multimodal distribution curve. Therefore, when a mixture of carbon black and graphite is used, a pore size distribution with two pore peaks (one carbon black peak and one graphite peak) can be obtained.
[0085] The MPL comprises conductive carbon particles, preferably carbon black or graphite, in a matrix consisting of a polymeric binder. Preferred binders are the above-mentioned fluoropolymers, in particular polytetrafluoroethylene (PTFE).
[0086] The microporous layer b) preferably has a thickness of 10 to 100 μm, particularly preferably a thickness of 20 to 50 μm. This thickness relates to the uncompressed state of the microporous layer b), ie before the GDL is installed in the fuel cell.
[0087] The presence of the MPL has a significant impact on the water balance of the fuel cell. Due to the high PTFE content and smaller pores of the MPL, oil displacement of the GDL and the electrode becomes difficult, since the MPL acts as a liquid water barrier and thus facilitates mass transport of gaseous reactants to the catalyst. It has been found that it may be advantageous that in a gas diffusion layer according to the invention the microporous layer has a characteristic gradient relative to the base surface (in the x, y plane) of its GDL.
[0088] The gas diffusion layer according to the invention preferably has a thickness of 80 to 1000 μm, particularly preferably a thickness of 100 to 500 μm (total thickness of fiber material a) and MPL b). This thickness relates to the uncompressed state of the GDL, ie before it is installed in a fuel cell.
[0089] Furthermore, the gas diffusion layer preferably has a high total porosity, which is preferably in the range from 20% to 80%, as determined, as described above, by helium density measurement and mercury porosimetry.
[0090] Characteristic gradient
[0091] As mentioned above, the planar fiber material a) and the microporous layer b) or both may have at least one property gradient.
[0092] The properties with gradient are in principle selected from
[0093] - the chemical composition of the planar fiber material a) and / or the microporous layer b),
[0094] - mechanical properties of the planar fiber material a) and / or the microporous layer b),
[0095] - the transport properties of the planar fiber material a) and / or the microporous layer b),
[0096] - A combination of the above.
[0097] The chemical properties of the planar fiber material a) and / or the microporous layer b) which may have a gradient include, for example, the content of hydrophobic agents, carbon particles, etc. In particular, the content of polytetrafluoroethylene, carbon black, graphite, graphene, carbon nanotubes (CNT), carbon nanofibers and mixtures thereof are included.
[0098] Mechanical properties of the planar fibrous material a) and / or the microporous layer b) which may have a gradient include, for example, density, mass per unit area, porosity and average pore size.
[0099] As mentioned above, g / m 3 The determination of the density in units of can be done by helium density measurement.
[0100] In g / m 2The area-based mass in units of Å can be determined according to ISO 9073-1 or EN 29073-1:1992.
[0101] The porosity of the GDL can be determined by various known measurement methods, such as mercury porosimetry or nitrogen BET method.
[0102] In order to generate a gradient in the mechanical properties, for example, a gradient can be provided for the compression behavior of the microporous layer by changing the composition of the microporous layer with respect to at least one of its materials. This also changes the connection to the electrode. Alternatively, a gradient in the mechanical properties can be generated by generating a gradient across the material width when the nonwoven is consolidated by a water jet. This influences the mechanical properties and the transport of water.
[0103] The transport properties of the planar fiber material a) and / or the microporous layer b) which may have a gradient include:
[0104] - the gas permeability of the planar fiber material a) and / or the microporous layer b),
[0105] - the liquid permeability of the planar fibrous material a) and / or the microporous layer b),
[0106] - the through resistance of the gas diffusion layer through the material plane,
[0107] - thermal resistance of the gas diffusion layer through the material plane,
[0108] - Dry diffusion length.
[0109] The gas permeability perpendicular to the plane of the material can be determined by Gurley measurement, for which an automated Gurley densitometer from Gurley Precision Instruments can be used. During the measurement, the permeability up to 100 cm is determined in seconds. 3 The air flows vertically through a 6.42 cm 2 The time for the GDL sample with a sample area of 1.34°. The air permeability determination according to Gurley is described in ISO 5636-5.
[0110] It can also be measured in L / m according to DIN EN ISO 9237:1995-12 2 The gas permeability of textile fabrics is measured in s.
[0111] The permeability of liquids perpendicular to the plane of the material, in particular the permeability of liquid water (liquid-water permeability "through the plane"), can be determined by so-called "filtration cells" or by the "Pennsylvania" method [see references ac]: [a] I. S. Hussaini and CY Wang, "Measurement of relative permeability of fuel cell diffusion media", Journal of Power Sources, Vol. 195, pp. 3830-3840, 2010; [b] J. D. Sole, "Study of water transport parameters and processes in gas diffusion layers of PEMFCs", Virginia Polytechnic Institute, 2008; [c] J. Benziger, J. Nehlsen, D. Blackwell, T. Brennan and J. Itescu, "Water flow in gas diffusion layers of PEM fuel cells", Journal of Membrane Science, Vol. 261, pp. 98-106, 2005.
[0112] To determine the through-plane (through-plane, TP) resistance, a method known from the literature as quasi-4-point measurement can be used. With this method it is not possible to detect the through-plane resistance of the MPL alone.
[0113] To determine the through-plane (through-plane, TP) thermal resistance, two known test methods can be used, namely the heat flow method or the laser flash method.
[0114] The dry diffusion length refers to the actual length of the distance that a gas molecule passes through the planar fiber material a) and / or the microporous layer b), in μm. It is measured using a fixed Wicke-Kallenbach cell.
[0115] In a preferred embodiment, the microporous layer (MPL) has at least one property gradient with respect to at least one chemical and / or physical property. The MPL has at least one property gradient relative to its base surface, i.e. in a top view or in the x, y plane. Optionally, the MPL may additionally have a property gradient perpendicular to its base surface, i.e. in the direction of the z-axis.
[0116] Preferably, the microporous layer has at least 2 discrete regions, preferably at least 3, especially at least 4, especially at least 5, especially at least 6, which differ in at least one property. In this embodiment, the change in properties between the regions is rapid. The various regions may all differ in the same property or (in the case of multiple different properties) the same property.
[0117] This is preferred. However, it is also possible that two or more regions differ in different properties. In a particular embodiment, the microporous layer has at least 2 discrete regions, preferably at least 3, in particular at least 4, in particular at least 5, in particular at least 6, which all differ in the same properties.
[0118] In a special embodiment, each individual region is substantially homogeneous in its properties. "Substantially homogeneous" is understood here to mean that only such property fluctuations occur in a region as would also occur if no gradients were intentionally generated (eg due to production).
[0119] In an alternative embodiment, the microporous layer has at least one continuous property gradient.
[0120] Preferably, the microporous layer has at least 2 transversely adjacent strips, preferably at least 3, especially at least 4, said strips differing in at least one property. In a particular embodiment, the microporous layer has at least 2 transversely adjacent strips, preferably at least 3, especially at least 4, said strips all differing in the same property. In particular, each individual strip is substantially homogeneous in its property.
[0121] Preferably, the properties of the microporous layer having a gradient are selected from
[0122] -Gurley gas permeability and
[0123] - Dry diffusion length.
[0124] A method for preparing a gas diffusion layer for a fuel cell
[0125] Another subject of the invention is a method for producing a gas diffusion layer for a fuel cell, the gas diffusion layer comprising a) a planar electrically conductive fiber material and b) a microporous layer on one surface of the fiber material, wherein the microporous layer has at least one property gradient with respect to the base surface of the gas diffusion layer (in the x, y plane) with respect to at least one chemical and / or physical property, wherein
[0126] i) providing a planar conductive fiber material a),
[0127] ii) coating the fiber material provided in step i) with a precursor to form a microporous layer, wherein the composition of the precursor is changed during coating to produce a gradient,
[0128] iii) subjecting the coated fiber material obtained in step ii) to a thermal aftertreatment.
[0129] With regard to suitable and preferred fiber materials a) used in step i), reference is made entirely to the preceding embodiments.
[0130] The precursor used in step b) preferably comprises at least one fluoropolymer, at least one carbon material and optionally at least one pore former. The fluoropolymer is preferably selected from polytetrafluoroethylene (PTFE) and tetrafluoroethylene-hexafluoropropylene copolymer (FEP). PTFE is preferably used. Preferably, the carbon material is selected from carbon black, graphite, graphene, carbon nanotubes (CNT), carbon nanofibers and mixtures thereof.
[0131] Preferably carbon black or graphite is used. In a particular embodiment, the precursor used in step b) comprises at least one pore former. Suitable pore formers are commercially available plastic particles, such as polymethyl methacrylate (PMMA). Suitable particle sizes are in the range of 10 to 100 μm.
[0132] Preferably, the proportion of pores in the finished microporous layer due to the use of the pore former is preferably 0 to 70 volume percent based on the total volume of pores in the finished microporous layer.
[0133] Preferably, the fiber material a) is coated with at least 2 laterally adjacent precursor strips of different composition, preferably at least 3, in particular at least 4, to form a microporous layer. The MPL order can be completed in a variety of ways. Although spraying, screen printing or Meyer rod processes are often used in discontinuous preparation, doctor blades, slit nozzles and engraved roller processes are preferably used in continuous coating. Here, the MPL layer thickness and penetration depth can be influenced by the coating process parameters and the viscosity of the coating. Finally, a new heat treatment is carried out, for example in a drying and sintering furnace. Here, drying can first be carried out at a temperature of 100 to 200° C. and then sintering can be carried out at a temperature of 300 to 500° C.
[0134] Fuel Cells
[0135] Another subject of the invention is a fuel cell comprising at least one gas diffusion layer as defined above or obtainable by a method as defined above.
[0136] In principle, the gas diffusion layer according to the invention is suitable for all common fuel cell types, in particular low-temperature proton exchange membrane fuel cells (PEMFC). Reference is made in its entirety to the previous statements regarding the construction of the fuel cell.
[0137] The invention has the advantage that the transport process through the gas diffusion layer can be specifically adapted to the gradient of the operating medium flowing through the fuel cell and / or the operating parameters of the fuel cell. To this end, at least one characteristic gradient of the gas diffusion layer generally corresponds to at least one of the characteristic gradient of the operating medium flowing through the fuel cell and / or the characteristic gradient of the operating parameters of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0138] Figure 1This is a top view of the GDL material prepared as described in Example 1. Four transversely adjacent strips with four different MPL pastes (Pastes 1 to 4) with a width of 7 to 8 cm were applied in the longitudinal direction to a fiber nonwoven in DIN A3 format (29.7×42 cm, MD stands for machine direction). A gas diffusion layer with the dimensions of 274.8×96.5 mm was punched out from the dried and sintered material, with its long side transverse to the machine direction. Figure 1 3 alternative punching positions are shown (GDL 1 to 3). The resulting GDL has a gradient of properties in the x-direction, with GDL 1 having 4 strips each having a different property, and GDL 2 and 3 having strips each having 3 different properties.
[0139] Figure 2 The current density distribution determined by Example 2 at the cathode of a membrane electrode unit according to the present invention having an MPL, wherein the membrane electrode unit has a characteristic gradient (circles), and the current density distribution determined by Example 2 at the cathode of a membrane electrode unit not according to the present invention, wherein the membrane electrode unit does not have a characteristic gradient (squares) are shown. DETAILED DESCRIPTION
[0140] The following examples are intended to explain the present invention but are not intended to limit the present invention in any way.
[0141] Example
[0142] Example 1:
[0143] Fabrication of a gas diffusion layer with x-direction property gradients
[0144] From 0.145mm thickness, 60g / m 2 The mass per unit area and 6.6mΩcm 2 From a commercially available conductive fiber nonwoven with a through resistance (through plane) at 1 MPa, sheets of DIN A3 format (29.7×42 cm) were punched out from a GDL roll in the longitudinal direction (machine direction, MD) and coated individually. To produce a microporous layer with a property gradient, four transversely adjacent strips with a width of 7 to 8 cm were applied in the longitudinal direction of the fiber nonwoven (see Figure 1 ). The paste had a composition according to Table 1. For the preparation, PTFE, various carbons and plastic particles were dispersed in distilled water as pore formers and applied to the fiber nonwoven by means of a doctor blade. Subsequently, the sheet was dried at 160° C. and sintered at 400° C. The resulting MPL loading was 15 to 22 g / m 2 depending on the strip. 2 .
[0145] Table 1
[0146]
[0147] 1) In each case, based on the total weight of the paste
[0148] From the obtained sheet, a gas diffusion layer having the dimensions of 274.8×96.5 mm was punched out, with its long side being transverse to the machine direction. Figure 1 3 alternative punching positions are shown. The obtained GDL has a property gradient in the x-direction, wherein GDL 1 has 4 strips with different properties, and GDL 2 and GDL 3 have 3 strips with different properties.
[0149] To prepare a fuel cell, as described below, the GDL is mounted so that the x-direction (long side) is in the direction of the direct connection between the supply and discharge of the running material to the flow distribution plate. Thus, in the case of a flow distribution plate with straight channels, the long sides of the GDL are parallel to the gas channels. However, in another flow field design, on the cathode side (air side) of the fuel cell, the supplied O2-rich fuel first contacts the MPL formed by paste 1, and the discharged O2-lean fuel contacts the MPL formed by paste 4.
[0150] In accordance with Figure 1 For each of the 4 strips in GDL 1, the Gurley gas permeability perpendicular to the plane of the material was determined according to ISO 5636-5 using a Gurley densitometer from Gurley Precision Instruments. The results are shown in Table 2.
[0151] In accordance with Figure 1 In GDL 1, in addition, for each of the four strips, the dry diffusion length was determined with the aid of a stationary Wicke-Kallenbach cell. The results are also shown in Table 2.
[0152] Table 2
[0153]
[0154] Example 2:
[0155] Current density distribution measurement
[0156] For the in situ measurement of the current density distribution, a membrane electrode unit (MEA) according to the invention was used on the one hand, the cathode of which was based on a gas diffusion layer (GDL), the microporous layer (MPL) of which had a characteristic gradient consisting of 4 transversely adjacent strips in the longitudinal direction of the fiber nonwoven (GDL 1 of Example 1). As anode, a conventional GDL was used, the MPL of which had no characteristic gradient. For the preparation, MPL paste 4 from Example 1 was used. For comparison, an MEA was used, the anode and cathode of which had a non-inventive GDL (without characteristic gradient) similar to the anode of the MEA according to the invention.
[0157] In the test system, hydrogen and oxygen were supplied to the MEA at a pressure of 1.5 bar in each case, the relative humidity (RH) of both gases before entering the measuring device was in each case 95%, and the fuel cell was operated at a temperature of 74° C. (coolant temperature at the cathode outlet). Excess hydrogen supply λ A is 1.2, the excess oxygen λ C is 2.0. The current density at the cathode is 1.8A / cm 2 The average value of the tap current density is determined using a measurement point matrix, which has 22 measurement positions in the direction of the main flow direction of the gas between the cathode input and the cathode output and 9 measurement positions perpendicular to the main flow direction of the gas (i.e. a total of 198 measurement points).
[0158] Figure 2 The current density distribution determined at the cathode of an MEA according to the invention (curve with circular symbols) and at the cathode of an MEA not according to the invention (curve with square symbols) is shown. For each measuring position 1 to 22 along the main flow direction of the gas, the curve shows the average value for 9 measuring positions perpendicular to the main flow direction of the gas. It can be seen that the GDL according to the invention has a more uniform current density distribution than the comparative GDL.
Claims
1. A gas diffusion layer for a fuel cell, characterized in that: The gas diffusion layer comprises: a) a planar conductive fiber material, and b) a microporous layer on one of the surfaces of the fiber material, wherein the gas diffusion layer has at least one property gradient with respect to its base area in the x,y plane with respect to at least one chemical and / or physical property, wherein the microporous layer has at least one characteristic gradient, wherein the microporous layer has at least two laterally adjacent strips that differ in at least one property, And wherein the total porosity of the gas diffusion layer is in the range of 20% to 80%, and the proportion of pores in the finished microporous layer due to the use of the pore former is 0 to 70 volume percent based on the total volume of pores in the finished microporous layer.
2. The gas diffusion layer according to claim 1, characterized in that The microporous layer has a continuous or jumpy property gradient, and the property gradient changes monotonically depending on the position.
3. The gas diffusion layer according to claim 1 or 2, characterized in that: The microporous layer has at least three regions that differ in at least one property.
4. The gas diffusion layer according to claim 1 or 2, characterized in that: The microporous layer has at least three laterally adjacent strips, the strips differing in at least one property.
5. The gas diffusion layer according to claim 1 or 2, characterized in that: The microporous layer has at least four laterally adjacent strips, the strips differing in at least one property.
6. The gas diffusion layer according to claim 1, characterized in that Each individual strip therein is substantially homogeneous in its properties.
7. The gas diffusion layer according to claim 4, characterized in that: Each individual strip therein is substantially homogeneous in its properties.
8. The gas diffusion layer according to claim 5, characterized in that Each individual strip therein is substantially homogeneous in its properties.
9. The gas diffusion layer according to claim 1 or 2, characterized in that: The properties with gradient are selected from: - the chemical composition of the planar conductive fiber material a) and / or the microporous layer b); - mechanical properties of the planar conductive fiber material a) and / or the microporous layer b); - the transport properties of the planar conductive fiber material a) and / or the microporous layer b); - A combination of the above.
10. A method for preparing a gas diffusion layer for a fuel cell, characterized in that: The gas diffusion layer comprises a) a planar electrically conductive fiber material and b) a microporous layer on one surface of the fiber material, wherein the microporous layer has at least one property gradient with respect to a base surface of the gas diffusion layer in an x,y plane with respect to at least one chemical and / or physical property, i) providing a planar conductive fiber material a), ii) coating the planar conductive fibrous material provided in step i) with a precursor to form a microporous layer, wherein the composition of the precursor is varied during coating to create a gradient, said fibrous material being coated with at least 2 laterally adjacent strips of the precursor to form the microporous layer, iii) subjecting the coated planar conductive fiber material obtained in step ii) to a thermal post-treatment, And wherein the total porosity of the gas diffusion layer is in the range of 20% to 80%, and the precursor used in step ii) includes at least one pore former, and the proportion of pores in the finished microporous layer due to the use of the pore former is 0 to 70 volume percent based on the total volume of pores in the finished microporous layer.
11. The method according to claim 10, characterized in that The composition of the precursor is varied during coating in such a way that the microporous layer has at least one monotonic property gradient relative to the base area of the gas diffusion layer in the x,y plane.
12. The method according to claim 10 or 11, characterized in that: The precursor used in step ii) comprises at least one fluorine-containing polymer, at least one carbon material and at least one pore former.
13. A fuel cell comprising at least one gas diffusion layer as defined in any one of claims 1 to 9 or a gas diffusion layer obtainable by a method as defined in any one of claims 10 to 12.
14. The fuel cell according to claim 13, characterized in that At least one characteristic gradient of the gas diffusion layer corresponds to at least one of a characteristic gradient of an operating medium flowing through the fuel cell and / or a characteristic gradient of an operating parameter of the fuel cell.
15. Use of a gas diffusion layer as defined in any one of claims 1 to 9 or obtainable by a method as defined in any one of claims 10 to 12 for producing a fuel cell having reduced current density fluctuations on the electrode surface.
16. Use of a gas diffusion layer as defined in any one of claims 1 to 9 or obtainable by a method as defined in any one of claims 10 to 12 for producing a fuel cell having reduced current density fluctuations on the cathode-side electrode surface.
Citation Information
Patent Citations
Gas diffusion layer and arrangement comprising two gas diffusion layers
DE102005022484A1
Improved membrane electrode units
EP2228857A1
Electrode, method of preparing the same, and fuel cell including the same
US20100255407A1
Conductive nonwoven
WO2002031841A2
Bipolar plate and a fuel cell comprising same
WO2015150533A1